2010
DOI: 10.1080/07315724.2010.10719897
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Intake and Depressive Symptomatology in a Greek Sample: An Epidemiological Analysis

Abstract: These results indicate that increased PUFA and MUFA concentrations are associated with diminished depressive symptomatology among apparently healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
21
1
2
Order By: Relevance
“…Conversion of ALA to DHA is higher in women than men [29]. But, some studies found no sex-based differences [30], some found opposite sex effect [31]. There have also been few studies that examined the effect of ω-3 PUFA supplementation on mood in young healthy populations.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of ALA to DHA is higher in women than men [29]. But, some studies found no sex-based differences [30], some found opposite sex effect [31]. There have also been few studies that examined the effect of ω-3 PUFA supplementation on mood in young healthy populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that women with higher consumptions of ALA were less likely to have depressive symptoms. A study by Panagiotakos et al (2010) in 853 healthy adults from the province of Attica found that increases in plasma total PUFA, total MUFA, total n-3 FA, DHA, EPA, LA and ALA were all associated with lower scores on Zung's Self-rating Depression Scale (40) . To the authors' knowledge, no one has previously shown an association between dietary intakes of ALA and reduced risk of depression using the SF-36 MH subscale and CESD-10 validated screening measures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in one randomized study magnesium proved to be comparably effective in the treatment of depression as imipramine, which is an extensively used, tricyclic and highly effective antidepressant drug [111]. Therefore it has been hypothesized that oral administration of magnesium might support an antidepressant effect [112,113].…”
Section: Special Nutritional Compounds Which Could Influence Depressimentioning
confidence: 99%
“…Increased polyunsaturated fatty acid (PUFA) and monounsaturated fatty acid (MUFA) concentrations, and high concentrations of plasma total n-3 fatty acids, docosahexaenoic acid, eicosapentaenoic acid, α-linoleic acid, and linoleic acid, were associated with lower scores in the depression scale used [113,114]. Accordingly, fish consumption has been associated with resilience to depression [115].…”
Section: Special Nutritional Compounds Which Could Influence Depressimentioning
confidence: 99%